Pu isotopes in the seawater off Fukushima Daiichi Nuclear Power Plant site within two months after the severe nuclear accident. (March 2019) - Men, Wu; Zheng, Jian; Wang, Hai; Ni, Youyi; Kumamoto, Yuichiro; Yamada, Masatoshi; Uchida, Shigeo
Abstract: The marine environment is complex, and it is desirable to have measurements for seawater samples collected at the early stage after the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident to determine the impact of Fukushima-derived radionuclides on this environment. Here Pu isotopes in seawater collected 33–163 km from the FDNPP site at the very early stage after the accident were determined (May 2011, within two months after the accident). The distribution and temporal variation of 239 Pu and 240 Pu were studied. The results indicated that both 239+240 Pu activity concentrations (from 0.81 ± 0.16 to 11.18 ± 1.28 mBq/m 3 ) and 240 Pu/ 239 Pu atom ratios (from 0.216 ± 0.032 to 0.308 ± 0.036) in these seawater samples were within the corresponding background ranges before the accident, and this suggested that Fukushima-derived Pu isotopes, if any, were in too limited amount to be distinguished from the background level in the seawater. The analysis of Pu isotopic composition indicated that the major sources of Pu in the seawater after the accident were still global fallout and the Pacific Proving Ground close-in fallout. The contribution analysis showed that the contributions of the Pacific Proving Ground close-in fallout in the water column of the study area ranged from 26% to 77% with the average being 48%. Graphical abstract: Image 1 Highlights: Plutonium isotopes in seawater at the very early stage of Fukushima accident were determined. Pu activities and atom ratios of the seawater samples 33–163 km off FDNPP site were provided. Fukushima-derived plutonium isotopes were too limited to be distinguished from the background. Contributions of the PPG Pu in the water column of the study area ranged from 26% to 77%. Abstract : The analysis of Pu isotopes in seawater samples within two months after the Fukushima accident indicated the accident-derived Pu contamination was negligible.